Muco supported prosthesis in the rehabilitation of a totally edentulous patient with cleft palate - Luján-Larreategui, Haydeé (2015)
The prosthetic rehabilitation of patients with cleft palate and completely toothless requires, among others, the preparation of a prosthesis with shutter. The main goal of treatment is to replace the missing structures and restore masticatory, swallow and speech functions. This article presents the rehabilitation of a patient with cleft palate of approximately 3 cm, connecting the oral and nasal cavities without involving the soft palate. It is described, clinical and laboratory aspects for the preparation of the appliance with which it was possible to restore the lost functions, sealing the buco nasal communication, resulting in great benefit for swallowing, speech and psychological recovery aspect.